Utilizing “Omic” Technologies to Identify and Prioritize Novel Sources of Resistance to the Oomycete Pathogen Phytophthora infestans in Potato Germplasm Collections - Van Weymers, Pauline S. M.; Baker, Katie; Chen, Xinwei; Harrower, Brian; Cooke, David E. L.; Gilroy, Eleanor M.; Birch, Paul R. J.; Thilliez, Gaëtan J. A.; Lees, Alison K.; Lynott, James S.; Armstrong, Miles R.; McKenzie, Gaynor; et al. (Frontiers in Plant Science, 2016)
The greatest threat to potato production world-wide is late blight, caused by the oomycete pathogen Phytophthora infestans. A screen of 126 wild diploid Solanum accessions from the Commonwealth Potato Collection (CPC) with P. infestans isolates belonging to the genotype 13-A2 identified resistances in the species S. bulbocastanum, S. capsicibaccatum, S. microdontum, S. mochiquense, S. okadae, S. pinnatisectum, S. polyadenium, S. tarijense, and S. verrucosum. Effector-omics, allele mining, and diagnostic RenSeq (dRenSeq) were utilized to investigate the nature of resistances in S. okadae accessions. dRenSeq in resistant S. okadae accessions 7129, 7625, 3762, and a bulk of 20 resistant progeny confirmed the presence of full-length Rpi-vnt1.1 under stringent mapping conditions and corroborated allele mining results in the accessions 7129 and 7625 as well as Avr-vnt1 recognition in transient expression assays. In contrast, susceptible S. okadae accession 3761 and a bulk of 20 susceptible progeny lacked sequence homology in the 5′ end compared to the functional Rpi-vnt1.1 gene. Further evaluation of S. okadae accessions with P. infestans isolates that have a broad spectrum of virulence demonstrated that, although S. okadae accessions 7129, 7625, and 7629 contain functional Rpi-vnt1.1, they also carry a novel resistance gene. We provide evidence that existing germplasm collections are important sources of novel resistances and that “omic” technologies such as dRenSeq-based genomics and effector-omics are efficacious tools to rapidly explore the diversity within these collections.